A Single‐Molecule‐Level Mechanistic Study of Pd‐Catalyzed and Cu‐Catalyzed Homocoupling of Aryl Bromide on an Au(111) Surface. Issue 14 (25th February 2014) - Adisoejoso, Jinne; Lin, Tao; Shang, Xue Song; Shi, Ke Ji; Gupta, Aditi; Liu, Pei Nian; Lin, Nian
Abstract On‐surface Pd‐ and Cu‐catalyzed CC coupling reactions between phenyl bromide functionalized porphyrin derivatives on an Au(111) surface have been investigated under ultra‐high vacuum conditions by using scanning tunneling microscopy and kinetic Monte Carlo simulations. We monitored the isothermal reaction kinetics by allowing the reaction to proceed at different temperatures. We discovered that the reactions catalyzed by Pd or Cu can be described as a two‐phase process that involves an initial activation followed by CC bond formation. However, the distinctive reaction kinetics and the CC bond‐formation yield associated with the two catalysts account for the different reaction mechanisms: the initial activation phase is the rate‐limiting step for the Cu‐catalyzed reaction at all temperatures tested, whereas the later phase of CC formation is the rate‐limiting step for the Pd‐catalyzed reaction at high temperature. Analysis of rate constants of the Pd‐catalyzed reactions allowed us to determine its activation energy as (0.41±0.03) eV.